Criss cross ebook - Perkins, Lynne Rae (2010)
Winner of the Newbery Medal • New York Times Bestseller • An ALA Notable Book • An ALA Best Book for Young Adults • School Library Journal Best Book • Booklist Editors' Choice • Kirkus Reviews Editors' Choice • Horn Book Fanfare Book • New York Public Library Book for the Teen Age In this acclaimed, award-winning, and timeless national bestseller, Newbery Medalist Lynne Rae Perkins explores the crisscrossing lives of four teenagers on the verge of adulthood. The unique format incorporates short vignettes, haiku, Q&As, and illustrations by the author. Written with love and humor, Criss Cross is an unforgettable story of friendship, family, and growing up. "It's hard to write a book this good. Lynne Rae Perkins makes it seem easy."—Kevin Henkes, New York Times–bestselling author of the Newbery Honor Books Olive's Ocean and The Year of Billy Miller "Brilliantly captures the adolescent-level Zen that thoughtful kids bring to their assessment of the world."—Bulletin of the Center for Children's Books (starred review) "Best of all are the understated moments, often private and piercing in their authenticity, that capture intelligent, likable teens searching for signs of who they are, and who they'll become."—ALA Booklist (starred review) "Written with humor and modest bits of philosophy, the writing sparkles with inventive, often dazzling metaphors."—Kirkus Reviews (starred review) "Like a lazy summer day, the novel induces that exhilarating feeling that one has all the time in the world."—The Horn Book (starred review) "A gentle story about a group of childhood friends facing the crossroads of life and how they wish to live it. Young teens will certainly relate."—School Library Journal (starred review)